Hydrogel nanoparticle encapsulated plasmid as a suitable gene delivery system - Rafiee, A.; Riazi-Rad, F.; Alimohammadian, M.H.; Havaskary, M.; Fatemi, S.M.R.; Pakpoor, B. (Цитология и генетика, 2015)
To facilitate the delivery of genetic material, the use of appropriate carriers such as polymers is necessary. Nanoparticles comprising of chitosan-alginate polymers were formed through pregel preparation method. Chi/Alg nanoparticles had a mean Z-Average diameter of 161.8 nm and mean zeta 29.3 mV, respectively. The ability of plasmid-complex in preventing DNA migration showed Chi/Alg nanoparticles have great capacity to maintain plasmid. The efficiency of nanoparticles for transfection of pEGFP-N1 plasmid in the cultured HEK 293 cells was measured by flow cytometry. Cell viability assays indicated that nanoparticles had no toxic effect on HEK 293 cells after 4 or 24 h. Our suitable candidate for gene delivery would be alg/chi nanoparticles. Для облегчения доставки генетического материала необходимо использование подходящих носителей, таких как полимеры. Наночастицы, состоящие из хитозан-альгинатных полимеров, были получены методом подготовки прегеля. Chi/Alg наночастицы имели средний диаметр 161.8 нм (Z-Average) и средний zeta-потенциал 29.3 mV. Отсутствие миграции ДНК во время электрофореза комплексов плазмиды с наночастицами показало, что Chi/Alg наночастицы могут удерживать плазмидную ДНК внутри комплекса. Эффективность наночастиц для трансфекции плазмиды pEGFP-N1 в культивируемые клетки HEK 293 была измерена с помощью жидкостной цитометрии. Тесты на жизнеспособ-ность клеток показали, что наночастицы не имели токсичного эффекта на клетки HEK 293 через 4 ч или 24 ч. Наночастицы Alg/Chi являются подходящим кандидатом для доставки генов.